A PHYSICAL ANALOGUE MODEL TO ANALYSE INTERACTIONS BETWEEN TENSILE STRESSES AND DISSOLUTION IN CARBONATE SLOPES - Casini S.; Martino S.; Petitta M.; Prestininzi A. (My University, 2006)
A physical analogue model was developed to analyse the relationship between tensional states in rock masses, seepage and karst processes. Use was made of an experimental apparatus consisting of two hydraulic circuits realized by drilling two holes into each of two blocks of sampled limestone from the central Apennines (Italy). A static load (208.85 kg) was applied to one of the blocks in order to elicit tensile stresses within it. Physical and chemical monitoring data showed that the main process involved was temperature-dependent CaCO3 dissolution. This process was more marked in the loaded block circuit, as Ca++ concentration in circulated water reached 54 mg/L, whereas only 28 mg/L was reached in the unloaded one. The interaction between load and dissolution caused the observed opening of microcracks, as confirmed by further increase of water loss and by dilution in the loaded block circuit, resulting in a decrease of Ca++ concentration. These findings were confirmed by recording additional water losses after increasing the load up to 445.05 kg. A finite difference numerical model showed that tensile stresses (max 20 kPa) within the loaded block were clustered at the intersection of the main joints with the flowpaths, thus representing points of preferential and accelerated dissolution.
Keywords: KARST; FRACTURED ROCKS; TENSIONAL STATES; LABORATORY EXPERIMENT; NUMERICAL MODELING